2020
DOI: 10.2174/1874836802014010370
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Performance Concept in the Construction Field: A Critical Review

Abstract: The performance concept in the construction field is very broad, can occur within the project scope and building, suggesting effective ways to evaluate according to the activities involved. Although a large number of studies on construction project performance (CPP) and performance-based building (PBB) have been conducted in the last decade, there remains a lack of consensus among researchers and professionals regarding how to integrate PBB-related activities into the construction project phases (design, plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
1
0
1
Order By: Relevance
“…Companies can focus on human resource development, empowerment, and collaboration to build a more diverse and innovative culture. Other studies such as (Santos et al, 2020) also suggested that a clear organizational structure encourages conducive work when carrying out project work.…”
Section: Resultsmentioning
confidence: 95%
“…Companies can focus on human resource development, empowerment, and collaboration to build a more diverse and innovative culture. Other studies such as (Santos et al, 2020) also suggested that a clear organizational structure encourages conducive work when carrying out project work.…”
Section: Resultsmentioning
confidence: 95%
“…Isso é um fator muito importante em ambientes escolares que sempre mudam com o passar do tempo, seguindo as metodologias pedagógicas e inovações tecnológicas.Há"Um projeto de construção passa por um ciclo de vida que envolve as etapas de iniciação, planejamento, execução e operação. O ciclo de vida do produto corresponde a uma série de fases pelas quais passa um projeto, desde o início até a conclusão"(SANTOS et al, 2020).. Notoriamente, e já exaustivamente dito, a fase de projeto é uma fase de decisões bastante estratégicas. Mas considerando o tempo de vida útil de uma edificação, a fase que compreende o uso representa uma maior parcela do tempo.…”
unclassified